2023
DOI: 10.3389/fpubh.2023.1155372
|View full text |Cite
|
Sign up to set email alerts
|

New insights into acupuncture techniques for poststroke spasticity

Abstract: With the trend of aging population getting more obvious, stroke has already been a major public health problem worldwide. As a main disabling motor impairment after stroke, spasticity has unexpected negative impacts on the quality of life and social participation in patients. Moreover, it brings heavy economic burden to the family and society. Previous researches indicated that abnormality of neural modulation and muscle property corelates with the pathogenesis of poststroke spasticity (PSS). So far, there sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…Meta-analysis showed in 11 trials that acupuncture seemed to be more effective than drugs for treatment of thalamic pain, as assessed by the VAS [mean difference (MD) = −1.06, 95% CI = −1.20 to −0.91, P < 0.00001], the present pain intensity score (MD = −0.27, 95% CI = −0.43 to −0.11, P = .001), the pain rating index (MD = −1.02, 95% CI = −1.41 to −0.63, P < 0.00001), and the total efficiency (RR = 1.31, 95% CI = 1.22 to 1.41, P < 0.00001) 23. Other studies have shown that acupuncture may reduce spasticity and help aphasia in stroke victims 24,25…”
Section: Miscellaneous Conditionsmentioning
confidence: 92%
“…Meta-analysis showed in 11 trials that acupuncture seemed to be more effective than drugs for treatment of thalamic pain, as assessed by the VAS [mean difference (MD) = −1.06, 95% CI = −1.20 to −0.91, P < 0.00001], the present pain intensity score (MD = −0.27, 95% CI = −0.43 to −0.11, P = .001), the pain rating index (MD = −1.02, 95% CI = −1.41 to −0.63, P < 0.00001), and the total efficiency (RR = 1.31, 95% CI = 1.22 to 1.41, P < 0.00001) 23. Other studies have shown that acupuncture may reduce spasticity and help aphasia in stroke victims 24,25…”
Section: Miscellaneous Conditionsmentioning
confidence: 92%
“…23 Other studies have shown that acupuncture may reduce spasticity and help aphasia in stroke victims. 24,25…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%
“…PSS generally refers to spasticity as part of the neurological component of spastic paresis [ 43 ]. PSS is a complex clinical phenomenon manifested by increased muscle tone and hyperactive reflexes, considered a neurologic problem and an indication of muscle disorder [ 44 ]. The stretch reflex consists of afferent nerve fibers, spinal motor neurons, and efferent nerve fibers, whose excitability is regulated primarily by excitatory and inhibitory signals originating downstream from above the spinal cord [ 45 – 48 ].…”
Section: The Pathophysiological Mechanisms Of Post-stroke Spasticitymentioning
confidence: 99%
“…
Fig. 1 Pathophysiology of post-stroke spasticity (PSS) associated with the corticospinal tract, modified from Wang et al [ 44 ]. The stretch reflex arc is mediated by excitatory connections between Ia afferent fibers from muscle spindles and the alpha-motor neurons innervating the same muscles they arise (indicated by the two gray neuron arrow loops in the figure).
…”
Section: The Pathophysiological Mechanisms Of Post-stroke Spasticitymentioning
confidence: 99%
See 1 more Smart Citation